The Abitur as a bureaucratic phenomenon: on the history of a Prussian examination practice and its ritualised inscription (1890–1970). - von Engelhardt, Kerrin (Paedagogica Historica, 2024)
This paper describes the Berlin Abitur examination in the twentieth century and its written documentation in files. By the late nineteenth century, the Abitur examination was fully established in Prussia and with it a graduation certificate that was obligatory for university entrance. Thus, the Abitur examination was part of the modern state entitlement system and an instrument to establish the state education monopoly. Thereafter, in every secondary school a new file was compiled for each class that took the exam every year. The resulting records provide a unique insight into the history of examination procedures. This article seeks to discuss the question of the Abitur files being simply products of bureaucratisation and rationalisation of examination practices at secondary schools, and the extent to which there was a ritualisation of the examination on paper. The building processes of the Abitur examination files in the twentieth century are reconstructed on the basis of a representative school archive located in Berlin.